"Optimizing communication modalities for project timeliness and quality: A case study of Fredmark builders and trading" - Rivera, Frances Bianca Yzobelle T. (Animo Repository, 2024)
This study investigated how the utilization and implementation of diverse communication methods and tools (digital, written, and face to face) by company employees affect the quality and timeliness of their projects. This study is positioned within the context of Fredmark Builders and Trading, a prominent ISO-certified construction company. Utilizing the Adaptive Structuration Theory (AST) framework, this study aims to identify the communication modalities Fredmark uses in achieving organizational objectives and the operational challenges the company encountered in achieving organizational objectives. This was conducted through a thematic analysis using a mixed-methods approach, which involved semi-structured interviews with key department managers and team members, document analysis, and participant observation, to identify patterns and themes related to Fredmark’s communication practices and their impact on project execution and completion. The findings reveal that Fredmark’s current communication practices, which involve a mix of email, chat applications, face-to-face communication, and written documents, play a crucial role in the timeliness and quality of projects. It is hoped that the data from this study will provide practical insights for large-scale construction companies aiming to refine their communication strategies to enhance project efficiency and quality.